(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article discusses the history of the formation and nature of the lexical-semantic term tolerance. The analysis of the concept of tolerance. The definition of the semantic aspect of the word tolerance frequency of application arespecified in the various branches of science. The distinctive feature in the vocabulary word tolerance, interpretation and application. Systematized synonymous and are close in meaning of the word in relation tolerance concepts presented their examples. Key words: tolerance, tolerance, meaning, lexical-semantic aspect, concept, term, religious tolerance, tradition, stability, content, scientific applications, ethnic, ethnos, culture, spirituality, religious backgrounds, worth.